Reflection technique for estimation of moisture hevea rubber latex content using rectangular patch antenna - Yahaya, Nor Zakiah; Abbas, Zulkifly; Hassan, Jumiah; Ansarudin, Farizah (Faculty of Engineering, Universiti Putra Malaysia, 2012)
In this paper, the designed microstrip patch antenna is employed to study reflection technique and predict moisture content of Hevea Rubber Latex. The rectangular patch sensor was designed to operate at microwave frequency range from 0.1 to 5 GHz on a RT/Duroid substrate with 6.15 ±0.015 permittivity and 1.27 mm thickness. The width and length of the rectangular patch antenna was 18 mm and 38 mm, respectively. The phase shift reflection coefficient, ΔӨ of rubber latex are obtained with moisture content at all selected frequencies. Estimation equations phase shift of reflection coefficient as a function of moisture content were developed at several selected frequencies. These equations were used to predict the amount of moisture content on Hevea latex based on the measured phase of reflection coefficient, ϕ using Agilent Professional Network Analyzer N5230A (PNA). The actual values of moisture content were obtained using standard oven drying method. The lowest mean relative error between actual and predicted moisture contents was 0.04 at 1 GHz.